Assessment of the plasmidome of an extremophilic microbial community from the Diamante Lake, Argentina - Perez, María Florencia; Saona, Luis Alberto; Farías, María Eugenia; Poehlein, Anja; Meinhardt, Friedhelm; Daniel, Rolf; Dib, Julián Rafael (Scientific reports, 2021)
Diamante Lake located at 4589 m.a.s.l. in the Andean Puna constitutes an extreme environment. It is exposed to multiple extreme conditions such as an unusually high concentration of arsenic (over 300 mg L −1 ) and low oxygen pressure. Microorganisms thriving in the lake display specific genotypes that facilitate survival, which include at least a multitude of plasmid-encoded resistance traits. Hence, the genetic information provided by the plasmids essentially contributes to understand adaptation to different stressors. Though plasmids from cultivable organisms have already been analyzed to the sequence level, the impact of the entire plasmid-borne genetic information on such microbial ecosystem is not known. This study aims at assessing the plasmidome from Diamante Lake, which facilitates the identification of potential hosts and prediction of gene functions as well as the ecological impact of mobile genetic elements. The deep-sequencing analysis revealed a large fraction of previously unknown DNA sequences of which the majority encoded putative proteins of unknown function. Remarkably, functions related to the oxidative stress response, DNA repair, as well as arsenic- and antibiotic resistances were annotated. Additionally, all necessary capacities related to plasmid replication, mobilization and maintenance were detected. Sequences characteristic for megaplasmids and other already known plasmid-associated genes were identified as well. The study highlights the potential of the deep-sequencing approach specifically targeting plasmid populations as it allows to evaluate the ecological impact of plasmids from (cultivable and non-cultivable) microorganisms, thereby contributing to the understanding of the distribution of resistance factors within an extremophilic microbial community.